The role of local level agency in a just green transition: the case of Rhodes University - Nel, Vanray (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The research uses a richly contextualised case study of Rhodes University to explore the role of local level agency in a just green transition. The central concept of the thesis is mainstreaming sustainability. Sustainability has become a core objective both at the macro and micro levels. The just green transition and triple bottom line are shorthand for these macro and micro concepts. At the macro level, there is increasing evidence suggesting that transitioning to a sustainable economy can be a key driver of economic development. At the micro level, the elements of the triple bottom line increasingly overlap, with sustainability no longer a separate goal, or a 'nice to have', but integral to organisational success. However, this potential is clearly not being realised, and sustainability often remains 'niche'. Lack of progress at the macro-level reinforces the importance of bottom-up, local level agency. In keeping with the broader micro-level literature, the case study strongly suggests that mainstreaming sustainability would have multiple benefits. These include reducing dependence on unreliable state-provided services and enhancing Rhodes University's standing as a genuinely transformative institution. The evidence suggests that there is a pure financial case for green investments, such as the construction of a solar farm at Rhodes University, even before accounting for the social and environmental benefits of such an initiative. This shifts the focus to why institutions like Rhodes University have not been proactive in mainstreaming sustainability. The document analysis and the interviews showed that there is an awareness of the importance and potential of mainstreaming sustainability. However, the funding squeeze is often misperceived as a binding constraint, and there is an absence of innovative thinking about how to finance projects with high returns, such as a solar farm. A theme amongst several of the interviewees was that the university should embrace a policy of enhancing small changes as a way of mainstreaming sustainability gradually. Even here, there are doubts about whether the organisational structure of the university will allow this. On the other hand, there are positive signs that the increasing sense of crisis means management and other key stakeholders are gradually shifting towards seeing the crucial importance of the university embracing a more proactive stance.
Keywords: Green economy; Just Transition; Clean energy -- South Africa -- Makhanda; Rhodes University; Triple bottom line; Sustainable development -- South Africa -- Makhanda